A Novel Late Effect of Chemotherapy: Fibro-Sclerotic Panniculopathy - MD, Carlesimo M; MD, Framarino Dei Malatesta M; MD, Fortuna MC; MD, Caro G; MD, Pigliacelli F; MD, D’Arino A; Prof., Rossi A (Archives of Clinical and Medical Case Reports, 2019)
Recently, increasing attention has been paid to late effects of chemotherapy. Even if cardiovascular and nervous toxicity is more often described [1-2], also skin and soft tissues are involved. Herein we reported 2 cases of chemotherapy-induced fibro-sclerotic panniculopathy.